The Role of English as a Foreign Language Teachers’ and Learners’ Emotions and Language Achievement and Success - Huang, Qian (Frontiers in Psychology, 2021)
It is preserved that one of the noteworthy influential subjects of success and achievement is emotions, and enhancing emotions is dominant in promoting the students’ language learning in the classroom. Although emotions are an integral part of the practices of both educators and students, their function has been sidelined due to the emphasis on intellectual instead of emotional scopes of foreign language learning. Therefore, the present theoretical review tries to refocus on the role of teachers’ and learners’ emotions and their effects on language success and achievement. Successively, the effectiveness of verdicts for educators, students, syllabus designers, and future researchers are deliberated.